Fostering Community Engagement at Koperasi Karyawan (Kopkar) Atma Jaya Makassar - Asri, Marselinus; Yori, Aurelius Kasimirus; Weleng, Veronika Natalie (JGEN : Jurnal Pengabdian Kepada Masyarakat, 2024)
This study outlines for social engagement the comprehensive financial audit process conducted by the Supervisor Team at Koperasi Karyawan (Kopkar) Atma Jaya Makassar. The audit aims to ensure the accuracy and reliability of financial statements, strengthen internal controls, and foster transparency and accountability within the cooperative. Through meticulous examination of financial records and rigorous testing of transactions, the audit identifies areas of strength and opportunities for improvement in financial management practices. The findings and recommendations from the audit are presented in the annual members cooperative meeting, facilitating open dialogue and enhancing trust and confidence among members and stakeholders.